Determinants of Sustainable Competitive Advantage of Malaysian Manufacturing Industries - - , Amir Samarrokhi (2010)
To address this issues, this thesis tried to introduce industry life cycle (ILC) as a time-dimension measure of earning-above average return for assessing the duration of SCA. Moreover, this study investigated if operations strategies and suitable resources can induce strong effects on the SCA. This thesis is an exploratory descriptive research.